Ultrastable Metallic Glass. (19th August 2013) - Yu, Hai‐Bin; Luo, Yuansu; Samwer, Konrad
<x xml:space="preserve">Abstract</x> A new metallic glass, which was created by vapour deposition at an appropriately high substrate temperature, shows exceptional thermal stability, and enhanced glass transition temperature and elastic modulus. Comparing this new material with other organic glasses prepared by similar routes and known as ultrastable glasses demonstrates the formation of ultrastable glassy materials correlates to the important concept of fragility. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>